Legal issues in information security - Grama, Joanna Lyn.; Books24x7, Inc. (Burlington, MA : Jones & Bartlett Learning, 2011)
This revised and updated second edition addresses the area where law and information security concerns intersect. Information systems security and legal compliance are now required to protect critical governmental and corporate infrastructure, intellectual property created by individuals and organizations alike, and information that individuals believe should be protected from unreasonable intrusion. Organizations must build numerous information security and privacy responses into their daily operations to protect the business itself, fully meet legal requirements, and to meet the expectations of employees and customers. --
Includes bibliographical references and index.
Text.
Available also in a print ed.
Mode of access: Internet via World Wide Web.
Digitized and made available by: Books24x7.com.
Keywords: Information storage and retrieval systems -- United States -- Security measures -- Law and legislation; Information storage and retrieval systems -- United States -- Law and legislation; Data protection -- Law and legislation -- United States; Electronic books; Electronic books